Assessing the effect of nursing stress factors on turnover intention among newly recruited nurses in hospitals in China - Lulin Zhou; Arielle Doris Kachie Tetgoum; Prince Ewudzie Quansah; Joseph Owusu‐Marfo (Wiley, 2022)
Abstract Aim This study sought to investigate some possible job stress factors that could influence newly recruited nurses' behaviour to either continue or discontinue their job with their organization. Design A cross‐sectional study design was adopted for this study. Method Using 654 responses from novice nurses working in 20 county Chinese hospitals, we estimated the effects of six job stressors from the perceived stress scale on the turnover intention with a structural equation model in AMOS version 21 software. Results The results showed that four stressors, stress from taking care of patients (β = 0.111, p < .01), stress from roles and workload (β = 0.129, p < .001), stress from co‐workers and daily life (β = 0.323, p < .001) and stress from lack of professional knowledge and skills (β = 0.137, p < .001), from the perceived stress scale had a significant impact on turnover intention among nurses.